Cross-Language Evolution of Divergent Collective Memory Around the Arab Spring - Lawson, H. Laurie; Keegan, Brian C. (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
The Arab Spring was a cascade of protests and uprisings across the Middle East and North Africa that toppled governments and escalated into prolonged conflicts in others. Collective memories of these events evolve unevenly across political, cultural, and linguistic contexts. Drawing on archived content from the Arabic and English Wikipedias (2011-2024), this study provides a generalizable framework for studying long-term collective memory processes on Wikipedia. We propose multilingual measures of salience, deliberation, contextualization, and consolidation and evaluate them using English and Arabic Wikipedia articles about the Arab Spring. Article size and wikilinks indicate sustained salience in both languages, though along different trajectories. Temporal clustering of wikilink inclusion reveals Stable, Debated, and Forgotten content, marking zones of consensus, contestation, and exclusion. Interlanguage links show limited cross-lingual alignment, with only a minority shared between editions. English pages consistently link back to the Arab Spring summary, while Arabic pages often do not, yielding uneven integration of the phenomenon into the encyclopedic network. These findings demonstrate Wikipedia’s role in long-term memory work and highlight cross-lingual biases relevant to multilingual knowledge systems.